IMPLEMENTASI PERAN MUHAFADZOH DALAM MENINGKATKAN INTELEKTUAL SANTRI PONDOK PESANTREN - soleh, Badrus; Khumaidi, Ahmad; Mutaqqin, Imam (Kelola: Journal of Islamic Education Management, 2024)
This research examines the role of muhafadzoh in improving the intellectuality of students at the Zainul Hasanain Islamic Boarding School. The Islamic boarding school is not only focused as a place for religious learning, but also as a center for intellectual development. The research uses a qualitative approach by collecting data through observation, interviews and document analysis. The research results show that the muhafadzoh's role has a significant impact in guiding classical learning, implementing literacy strengthening strategies, and collaborating with education authorities. Good collaboration between muhafadzoh and education not only increases students' religious knowledge, but also enriches their insight into science. These findings indicate that the role of muhafadzoh has a central role in creating a holistic educational environment that supports the overall intellectual development of students.